Analisis Karakteristik Pekarangan dalam Mendukung Penganekaragaman Pangan Keluarga di Kabupaten Bogor - Azra, Azka Lathifah Zahratu; Arifin, Hadi Susilo; Astawan, Made; Arifin, Nurhayati HS (http://arl-faperta.ipb.ac.id/, 2014)
Pekarangan is a type of traditional Indonesian home gardens that utilize the land around the house with the status and clear boundaries. Pekarangan in rural areas have high agrobiodiversity, good agroecosystem and should be optimized as an area to meet the needs of daily life, especially to support the diversification of food consumption of the household. Therefore, the purpose of this study is to analyze the ecology characteristics of pekarangan to support food consumption diversification of the household. The study was conducted in Bogor Regency, which located in altitudes at 165 – 460 m height with high level of urbanization, from December 2013 to June 2014. Diversity of food in pekarangan, specially the crops and livestocks, is the focus of this research. The results of the study showed that the most common crops in Bogor Regency are vegetables, fruits, and spices plants. Analysis of plant diversity index showed that the pekarangan in Bogor Regency has a diversity in the mid category (1.95) with the dominance of seasonal crops. Diversification of food in pekarangan can be done by optimizing the existing area, utilization of all zoning for the cultivation of diverse functions crops and livestock. For diversification of food consumption, the owner should use different types of food, as well as considering the crop calendar to a wide variety of food that can be consumed on a daily basis. Therefore, it's necessary to educate the housewives about the potency of diversification crops in pekarangan for consumption, strong motivation and assistance from the government, as well as optimizing the role of KWT group to optimize the role of pekarangan for the diversification of food.